Fathers of Genius: the Ambiguities of Power in Relations with their Fathers for Three Women Writers, Maria Edgeworth, Elizabeth Barrett Browning and Virginia Woolf - Danytė, Milda (Acta humanitarica academiae Saulensis, 2019)
18th and 19th century British social norms made it very difficult for talented women to become published writers: many of those who were successful owed a good deal to the help of their fathers. This article considers the particular nature of such father-daughter relationships, focusing on three women who became literary celebrities of their time, Maria Edgeworth, Elizabeth Barrett Browning and Virginia Woolf. It also poses two questions: why the fathers in these cases acted against the rules for women by encouraging their daughters, and what price the three men paid for breaking rules. Research on the fathers, Richard Edgeworth, Edward Barrett and Leslie Stephen, reveals similarities among them. Although comfortably middle-class, they were still marginal in their societies; all had ambitions of their own which they failed to realize; and all devoted unusual amounts of time to their families. All of them encouraged their daughters’ literary development, in particular by giving them access to contemporary literature collected in their private libraries. Both Edgeworth and Barrett did a great deal to promote their daughters’ writings, while Stephen provided the model of a possible literary career. However, at a certain stage the fathers became less liberal, returning to the idea that women should be subordinate within their families. Maria Edgeworth had to write educational works to be allowed to write novels. Elizabeth Barrett Browning published her strongest works only after eloping with Robert Browning. Virginia Woolf was not able to write her modernist fiction until her father died. As for the fathers, Barrett and Stephen especially felt betrayed by their daughters in their later life.
Keywords: father and daughter relationships; 18th and 19th century women writers; restrictions on women; Maria Edgeworth; Elizabeth Barrett Browning; Virginia Woolf; Richard Edgeworth; Edward Barrett; Leslie Stephen